FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEINGINAN BERHENTI MEROKOK DAN MEMANFAATKAN LAYANAN KESEHATAN PADA PASIEN DI RUMAH SAKIT UNIVERSITAS UDAYANA - Nasichah, Mahfudlotun; Suarjana, I Ketut (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025, 2025)
ABSTRACT Smoking behavior is currently an activity that is starting to be considered normal by most people. The high prevalence of smokers will have a negative impact on health, namely causing various diseases, especially NCDs. One of the effective efforts to reduce these adverse effects is to quit smoking. This study aims to analyze the factors associated with the desire to quit smoking and utilize health services in patients at Udayana University Hospital. This study was an observational study with a cross sectional descriptive design conducted in March-June 2023 at Udayana University Hospital. The population of this study were patients with smoking status at Udayana University Hospital. Data collection techniques were carried out through an interview process with the help of an online questionnaire. Data analysis was performed by univariable and bivariable analysis. The results showed that the factors associated with the desire to quit smoking and utilize health services in patients were perceived need for healthcare support (OR=8.61; 95% CI=3.35-22.10; p<0.01) and perceptions of smoking policies (OR=3.36; 95% CI=1.28-8.79; p=0.01). Keywords: smoking behavior, desire to quit smoking, smoking cessation services